PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN HONDA MOBILIO PADA HONDA SEMARANG CENTER - Retno Dwi Hartanti; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2017)
Transportation is a necessity for humans to make it easier to perform daily activities, transportation needs will continue to increase over time especially land transportation, which is car. Honda issued a product low MPV segment that Honda Mobilio launched in 2014. The level of sales of Honda Mobilio in Honda Semarang Center experience fluctuating levels of sales. The purpose of this study was to determinethe extent of the effect of product quality, service quality, and the price on purchasing decision Honda Mobilio. Type of this research is explanatory research with 92 respondents drawn using purposive sampling technique. The technique of collecting data used questionnaires and interviews. The analytical method used in this research using regression analysis with SPSS version 20.0. The results showed that the product quality has an effect on purchasing decisions with a correlation coefficient of 0.413 and a coefficient of determination of 17.1%, the quality of service has an effect on purchasing decisions with a correlation coefficient of 0.634 and a coefficient of determination of 40.2%, the price has an effect on purchasing decisions with coefficients 0,703 and determination correlation coefficient of 49.4%. Product quality, service quality, and price together have an effect on purchasing decisions by the equation Y = 2,435 + 0,202 X1 + 0,208 X2 + 0,924 X3. This means that the effect of product quality, service quality, and the price will increase purchasing decisions. Advised for the company based on this research that Honda Semarang Center should be review about security level Honda Mobilio, improve and enhance the timeliness of product delivery to the hands of consumers, review and improve the product quality and then giving promotions to attract consumers.